Artemis Fowl : the time paradox - Colfer, Eoin. (New York : Hyperion Books for Children, 2008)
Artemis's mother has contracted a deadly disease -- and the only cure lies in the brain fluid of African lemurs. Unfortunately, Artemis himself was responsible for making the lemurs extinct five years ago. Now he must enlist the aid of his fairy friends to travel back in time and save them. Not only that, but he must face his deadliest foe yet...his younger self.
"Miramax books."
Keywords: Lemurs -- Juvenile fiction; Magic -- Juvenile fiction; Fairies -- Juvenile fiction; Space and time -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction